Pengaruh Penerapan Model Problem Based Learning Terhadap Hasil Belajar Subtema Bersyukur Atas Keberagaman - Sri Utari; Teti Rostikawati; Nur Hikmah (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the effect of the Problem Based Learning model on learning outcomes in the Sub-theme of Gratitude for Diversity. This type of research is a quasi-experimental quantitative research method. Based on data analysis, there is a difference between the average pretest and posttest learning outcomes. The research results obtained were 2.34741 > 2.00665 so that H0 was rejected and Ha was accepted. In addition, the learning outcomes proved that the average N-Gain value in the experimental group was 66 while the average N-Gain value in the control group was 57. It can be stated that the Problem Based Learning model has an influence on learning outcomes in the sub-theme of gratitude for diversity in class IV at SDN Kedung Halang 5 Bogor City.